Flame-retardant UV curing adhesive as well as preparation method and application thereof

By using the combination of P-N type flame retardant and synergistic agent in the flame retardant adhesive, the problem of poor flame retardant performance of existing flame retardant adhesives is solved, and efficient flame retardant effect and excellent bonding are achieved. performance.

CN119177086AActive Publication Date: 2024-12-24KUNSHAN BYE MACROMOLECULE MATERIAL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411675984.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2024-12-24
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

The flame retardant performance of existing flame retardant adhesives is poor, especially the halogen flame retardant releases toxic gases, the phosphorus flame retardant preparation is complex and costly, the nitrogen flame retardant is low in flame retardant efficiency, and the carbon resistance is The problem of large amounts of fuel agents need to be added to achieve flame retardant effects.

Method used

Using P-N type flame retardant and synergist, through specific chemical reactions and mass ratio control, a combination of P-N type flame retardant and synergist with unique structure is formed to prepare flame retardant UV curing adhesives, including Acrylic resin, reactive diluent, polyvinyl alcohol, mercaptopropyl isobutyl cage silsesquioxane, photoinitiator, P-N type flame retardant and synergistic agent to form a multivariate flame retardant system.

Benefits of technology

The flame retardant performance of the adhesive has been significantly improved, with an oxygen index of more than 35%. Through the V-0 level of UL-94 vertical combustion test, it can achieve post-ignition expansion and smoke suppression, and there is no dripping during the combustion process, and there is no obvious smoke generation. Excellent connection performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119177086A_ABST
    Figure CN119177086A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of adhesives, and particularly discloses a flame-retardant UV curing adhesive as well as a preparation method and application thereof. The flame-retardant UV curing adhesive is prepared from the following raw materials in parts by weight: 40 to 80 parts of acrylic resin, 20 to 50 parts of reactive diluent, 20 to 30 parts of polyvinyl alcohol, 10 to 20 parts of mercaptopropyl isobutyl polyhedral oligomeric silsesquioxane, 3 to 10 parts of photoinitiator, 10 to 20 parts of P-N type flame retardant, 3 to 8 parts of synergist and 0.5 to 2 parts of defoaming agent. And a multi-element flame-retardant system can be formed between the P-N type flame retardant and the synergist, so that the flame retardant property of the adhesive is improved, the oxygen index of the adhesive reaches 35% or above, after-combustion expansion and smoke suppression are realized through a UL-94 vertical combustion test V-0 level, and no dripping or obvious smoke is generated in the combustion process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of adhesives, and more specifically, to a flame retardant UV curing adhesive and a preparation method and application thereof. Background Art

[0002] Flame retardant adhesives are mainly composed of basic adhesives, flame retardants, fillers and additives. Basic adhesives are one of the main components of flame retardant adhesives. Flame retardants, fillers and additives are mixed together and have good bonding properties. Flame retardants are the core components of flame retardant adhesives and play a flame retardant role when a fire occurs. There are many types of flame retardants, but different types of flame retardants also have certain problems in the use process. For example, although halogen flame retardants have high flame retardant efficiency, the toxic gases such as hydrogen bromide released during the combustion process seriously endanger people's lives and health, which is not conducive to the practical application of halogen flame retardants. Phosphorus flame retardants have the advantages of low toxicity and good dispersibility, but some phosphorus flame retardants are complicated to prepare and costly, which is not conducive to large-scale production. Nitrogen flame retardants have the advantages of low smoke and high stability, but the flame retardant efficiency is not high when used alone, and they need to be used in combination with other flame retardants. Carbon flame retardants have the effects of corrosion resistance and smoke suppression, but some flame retardants are complicated to prepare and the process is dangerous. Metal oxide flame retardants are widely available, have good thermal stability, and produce little smoke when burned, but their flame retardant efficiency is low. A large amount of flame retardant needs to be added to achieve the flame retardant effect, which can easily cause the deterioration of the mechanical properties of the material.

[0003] At present, invention patent CN118421246A discloses a flame retardant adhesive composition whose raw materials include epoxy resin, acrylic copolymer, ammonium polyphosphate, carboxymethyl cellulose calcium, expanded graphite, curing agent, diluent and defoaming agent; and the expanded graphite is modified with ferrocenyl ketone; the flame retardant performance of the obtained adhesive still needs to be improved; therefore, the present invention proposes a flame retardant UV curing adhesive and its preparation method and application. Summary of the invention

[0004] In order to solve the problem of poor flame retardancy of existing adhesives, the present invention provides a flame retardant UV curing adhesive and a preparation method and application thereof.

[0005] In a first aspect, the present invention provides a flame retardant UV curing adhesive, which adopts the following technical solution: A flame retardant UV curing adhesive comprises the following raw materials in parts by weight: 40-80 parts of acrylic resin, 20-50 parts of active diluent, 20-30 parts of polyvinyl alcohol, 10-20 parts of mercaptopropyl isobutyl cage silsesquioxane, 3-10 parts of photoinitiator, 10-20 parts of PN type flame retardant, 3-8 parts of synergist and 0.5-2 parts of defoamer.

[0006] Preferably, the preparation method of the PN type flame retardant comprises the following steps: Add 1,4-bis(3-aminopropyl)piperazine to ethanol, mix well, slowly add phytic acid aqueous solution, add dropwise within 5-10 minutes, react at 60-70°C for 10-20 hours, centrifuge, wash, dry and purify to obtain PN flame retardant.

[0007] Preferably, the mass ratio of the aqueous solution of 1,4-bis(3-aminopropyl)piperazine, ethanol and phytic acid is 6g:40-60g:13.2-22g; The content of phytic acid in the aqueous solution of phytic acid is 30-50wt%.

[0008] Preferably, the synergist is at least one of α-zirconium phosphate, organic bentonite, and calcium metaborate.

[0009] Preferably, the synergist is obtained by mixing α-zirconium phosphate, organic bentonite and calcium metaborate in a mass ratio of 1:5:4.

[0010] Preferably, the reactive diluent is at least one of isooctyl acrylate, dipropylene glycol diacrylate, isobornyl acrylate, tetraethylene glycol dimethacrylate, neopentyl glycol diacrylate, diethylene glycol diacrylate, glycidyl methacrylate, and dodecyl methacrylate.

[0011] Preferably, the photoinitiator is at least one of 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methylphenyl acetone, (2,4,6-trimethylbenzoyl) diphenyl phosphine oxide, ethyl 2,4,6-trimethylbenzoyl phenyl phosphonate, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy) phenyl]-1-propanone, and benzophenone.

[0012] Preferably, the defoaming agent is at least one of BYK-051, BYK-530, BYK-025, BYK-1723, BYK-1724, BYK-1611, and BYK-1617.

[0013] In a second aspect, the present invention provides a method for preparing a flame retardant UV curing adhesive, using the following technical solution: A method for preparing a flame retardant UV curing adhesive comprises the following steps: According to the formula, acrylic resin, active diluent and defoamer are mixed, heated to 50-70°C, stirred for 1-2 hours, heated to 80-90°C, polyvinyl alcohol, mercaptopropyl isobutyl cage silsesquioxane, PN flame retardant and synergist are added, and stirred for 1-2 hours; cooled to 50-75°C, photoinitiator is added, and stirred for 1-2 hours to obtain a flame retardant UV curing adhesive.

[0014] In a third aspect, the present invention provides an application of a flame retardant UV curing adhesive, using the following technical solution: A flame retardant UV curing adhesive is used in pressure sensitive tapes.

[0015] In summary, the present invention has the following beneficial effects: 1. The raw materials of the flame retardant UV curing adhesive of the present invention include acrylic resin, reactive diluent, polyvinyl alcohol, mercaptopropyl isobutyl cage silsesquioxane, photoinitiator, PN type flame retardant, synergist, and defoamer. The raw materials interact with each other, and the obtained flame retardant UV curing adhesive has excellent flame retardant properties, good UV curing characteristics, and outstanding bonding properties, and can be widely used in pressure-sensitive tapes.

[0016] 2. The present invention utilizes the reaction between the phosphate group in phytic acid and the amino group in 1,4-bis(3-aminopropyl)piperazine, and strictly controls the mass ratio and reaction conditions of the two, so that each PN-type flame retardant molecule contains three [-NH-P=O(OH)-O-] bonds, forming a PN-type flame retardant with a unique structure.

[0017] The PN type flame retardant of the present invention will lose the terminal amino group during the heating process, and produce non-flammable nitrogen-containing gas. The non-flammable gas can not only increase the height of the carbon layer, but also play a strong carbon layer barrier role in the condensed phase, isolating the transfer of oxygen and heat; it can also dilute the concentration of the combustible gas and prevent the transfer of flames in the gas phase; in addition, the PN type flame retardant has a plurality of highly active PN bonds, and the electron-hole pairs in the PN bonds have the ability to absorb and release energy, which will promote the formation of a continuous, dense and difficult-to-burn carbon layer in the condensed phase by the decomposition products of the adhesive, thereby isolating the transfer of oxygen and heat, and greatly improving the flame retardant properties of the adhesive. In addition, the spatial structure of the PN type flame retardant of the present invention is unique, and it can be better compatible with other raw materials and improve the bonding properties of the adhesive.

[0018] 3. The synergist of the present invention is at least one of α-zirconium phosphate, organic bentonite, and calcium metaborate. α-zirconium phosphate catalyzes polymer cross-linking to form carbon at high temperature, forming a dense protective layer, effectively blocking the transfer of oxygen and heat, and reducing the combustion rate; organic bentonite has good thickening, thixotropy and other properties, which can improve the fluidity of the material and the dispersibility of the flame retardant, thereby enhancing the flame retardant effect; calcium metaborate can lose its own structural water at high temperature, and the water vapor produced plays the role of heat absorption cooling and dilution of oxygen in the air. At the same time, it can also form a glassy expansion layer during combustion, which can inhibit the generation of combustible gas and prevent oxidation reaction and thermal decomposition. The present invention further prefers a mixture of α-zirconium phosphate, organic bentonite and calcium metaborate in a specific mass ratio as a synergist. The three of them jointly enhance the flame retardant effect of the adhesive through synergistic effects such as catalytic carbonization and barrier effect, heat absorption cooling and oxygen dilution, and improvement of flame retardant dispersibility.

[0019] 4. The PN flame retardant of the present invention and the synergist can form a multi-component flame retardant system, improve the flame retardant properties of the adhesive, make its oxygen index reach more than 35%, pass the UL-94 vertical combustion test V-0 level, achieve post-combustion expansion and smoke suppression, and there is no dripping and no obvious smoke generation during the combustion process.

[0020] 5. The preparation method of the flame-retardant UV curing adhesive of the present invention has simple steps and low cost. In the preparation process, various process parameters are controlled to promote the interaction between the raw materials. Under UV light, a high-performance adhesive can be obtained, which has the characteristics of good flame retardant effect, anti-dripping, low smoke emission, excellent bonding performance, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings: Figure 1 This is the nuclear magnetic resonance hydrogen spectrum of the PN type flame retardant provided in Preparation Example 1 of the present invention. DETAILED DESCRIPTION

[0022] The present invention is further described in detail below with reference to the embodiments.

[0023] The materials and reagents used in the present invention, unless otherwise specified, can be obtained from commercial sources; among them, mercaptopropyl isobutyl cage silsesquioxane, CAS No. 480438-85-5, was purchased from Xi'an Qiyue Biotechnology Co., Ltd.; 1,4-bis (3-aminopropyl) piperazine, CAS No. 7209-38-3, was purchased from Tesco Chemical Co., Ltd.; acrylic resin, CAS No. 94188-59-7, was purchased from Shanghai MacLean Biochemical Technology shares; polyvinyl alcohol, CAS No. 9002-89-5, Mw13000-23000, 98% hydrolysis, purchased from Shanghai McLean Biochemical Technology Co., Ltd.; α-zirconium phosphate, CAS No. 13772-29-7, average particle size 2μm, purchased from Shanghai McLean Biochemical Technology Co., Ltd.; organic bentonite (DK2) was purchased from Zhejiang Fenghong New Materials Co., Ltd.; calcium metaborate, CAS No. 13701-64-9, 39-44% B2O3 basis, 31-37% CaO basis, purchased from Shanghai McLean Biochemical Technology Co., Ltd.; piperazine pyrophosphate, CAS No. 66034-17-1, purchased from Zhongshan Dixin Chemical Co., Ltd.

[0024] Preparation Example 1-4 provides a method for preparing a PN type flame retardant.

[0025] Preparation Example 1: The preparation method of PN type flame retardant comprises the following steps: Add 6 g of 1,4-bis(3-aminopropyl)piperazine to 40 g of ethanol, mix well, then slowly add 22 g of phytic acid aqueous solution (phytic acid content is 30 wt%), add dropwise within 10 min, react at 60 ° C for 10 h, centrifuge, wash, dry, recrystallize with 100 mL of methanol / tetrahydrofuran (volume ratio is 1:3), filter and dry to obtain 9.98 g of PN flame retardant (purity 99.9%, yield 82.8%).

[0026] Preparation Example 2: The preparation method of PN type flame retardant comprises the following steps: Add 6 g of 1,4-bis(3-aminopropyl)piperazine to 50 g of ethanol, mix well, slowly add 16.5 g of phytic acid aqueous solution (phytic acid content is 40 wt%), add dropwise within 8 min, react at 65 ° C for 15 h, centrifuge, wash, dry, recrystallize with 100 mL of methanol / tetrahydrofuran (volume ratio of 1:3), filter and dry to obtain 10.13 g of PN flame retardant (purity 99.9%, yield 84.0%).

[0027] Preparation Example 3: The preparation method of PN type flame retardant comprises the following steps: Add 6 g of 1,4-bis(3-aminopropyl)piperazine to 60 g of ethanol, mix well, slowly add 13.2 g of phytic acid aqueous solution (phytic acid content is 50 wt%), add dropwise within 5 min, react at 70 ° C for 20 h, centrifuge, wash, dry, recrystallize with 100 mL of methanol / tetrahydrofuran (volume ratio of 1:3), filter and dry to obtain 10.29 g of PN flame retardant (purity 99.9%, yield 85.3%).

[0028] Preparation Example 4: PN type flame retardant is prepared by the following method: 1.8 g of ethylenediamine was added to 40 g of ethanol, and after mixing evenly, 22 g of phytic acid aqueous solution (phytic acid content is 30 wt%) was slowly added. After the dropwise addition was completed within 10 min, the mixture was reacted at 60 ° C for 10 h. After the reaction was completed, the mixture was centrifuged, washed, dried, recrystallized with 100 mL of acetone, filtered, and dried to obtain 6.78 g of PN flame retardant (purity 99.9%, yield 86.3%).

[0029] Embodiment 1-8 provides a flame retardant UV curing adhesive and a preparation method thereof.

[0030] Embodiment 1:

[0031] A flame retardant UV curing adhesive, comprising the following raw materials in parts by weight: 40 parts of acrylic resin, 20 parts of reactive diluent, 20 parts of polyvinyl alcohol, 10 parts of mercaptopropyl isobutyl cage silsesquioxane, 3 parts of photoinitiator, 10 parts of PN type flame retardant, 3 parts of synergist, and 0.5 parts of defoamer; Wherein, the active diluent is isooctyl acrylate; the photoinitiator is 1-hydroxycyclohexyl phenyl ketone; the PN type flame retardant is prepared by Preparation Example 1; the synergist is organic bentonite; the defoamer is BYK-051; A method for preparing a flame retardant UV curing adhesive comprises the following steps: According to the formula, acrylic resin, active diluent and defoamer are mixed, the temperature is raised to 50°C, stirred for 1 hour, the temperature is raised to 80°C, polyvinyl alcohol, mercaptopropyl isobutyl cage silsesquioxane, PN type flame retardant and synergist are added, and stirred for 1 hour; the temperature is lowered to 50°C, photoinitiator is added, and stirred for 1 hour to obtain a flame retardant UV curing adhesive.

[0032] Embodiment 2:

[0033] A flame retardant UV curing adhesive, comprising the following raw materials in parts by weight: 60 parts of acrylic resin, 35 parts of reactive diluent, 25 parts of polyvinyl alcohol, 15 parts of mercaptopropyl isobutyl cage silsesquioxane, 6 parts of photoinitiator, 15 parts of PN type flame retardant, 5.5 parts of synergist, and 1 part of defoamer; The active diluent is obtained by mixing isobornyl acrylate and glycidyl methacrylate in a mass ratio of 1:1; the photoinitiator is ethyl 2,4,6-trimethylbenzoylphenylphosphonate; the PN flame retardant is obtained by Preparation Example 2; the synergist is α-zirconium phosphate; and the defoamer is BYK-1724; A method for preparing a flame retardant UV curing adhesive comprises the following steps: According to the formula, acrylic resin, active diluent and defoamer are mixed, the temperature is raised to 60°C, stirred for 1.5 hours, the temperature is raised to 85°C, polyvinyl alcohol, mercaptopropyl isobutyl cage silsesquioxane, PN type flame retardant and synergist are added, and stirred for 1.5 hours; the temperature is lowered to 65°C, photoinitiator is added, and stirred for 1-2 hours to obtain a flame retardant UV curing adhesive.

[0034] Embodiment 3:

[0035] A flame retardant UV curing adhesive, comprising the following raw materials in parts by weight: 80 parts of acrylic resin, 50 parts of reactive diluent, 30 parts of polyvinyl alcohol, 10-20 parts of mercaptopropyl isobutyl cage silsesquioxane, 10 parts of photoinitiator, 20 parts of PN type flame retardant, 8 parts of synergist, and 2 parts of defoamer; The active diluent is obtained by mixing isooctyl acrylate, tetraethylene glycol dimethacrylate and dodecyl methacrylate in a mass ratio of 1:1:1; the photoinitiator is 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone; the PN flame retardant is obtained by Preparation Example 3; the synergist is calcium metaborate; and the defoamer is BYK-025; A method for preparing a flame retardant UV curing adhesive comprises the following steps: According to the formula, acrylic resin, active diluent and defoamer are mixed, the temperature is raised to 70°C, stirred for 2 hours, the temperature is raised to 90°C, polyvinyl alcohol, mercaptopropyl isobutyl cage silsesquioxane, PN type flame retardant and synergist are added, and stirred for 2 hours; the temperature is lowered to 75°C, photoinitiator is added, and stirred for 2 hours to obtain a flame retardant UV curing adhesive.

[0036] Embodiment 4:

[0037] Example 4 is different from Example 1 only in that the synergist is obtained by mixing α-zirconium phosphate and organic bentonite in a mass ratio of 1:1, as follows: A flame retardant UV curing adhesive, comprising the following raw materials in parts by weight: 40 parts of acrylic resin, 20 parts of reactive diluent, 20 parts of polyvinyl alcohol, 10 parts of mercaptopropyl isobutyl cage silsesquioxane, 3 parts of photoinitiator, 10 parts of PN type flame retardant, 3 parts of synergist, and 0.5 parts of defoamer; The active diluent is isooctyl acrylate; the photoinitiator is 1-hydroxycyclohexyl phenyl ketone; the PN flame retardant is prepared by Preparation Example 1; the synergist is prepared by mixing α-zirconium phosphate and organic bentonite in a mass ratio of 1:1; the defoamer is BYK-051; A method for preparing a flame retardant UV curing adhesive comprises the following steps: According to the formula, acrylic resin, active diluent and defoamer are mixed, the temperature is raised to 50°C, stirred for 1 hour, the temperature is raised to 80°C, polyvinyl alcohol, mercaptopropyl isobutyl cage silsesquioxane, PN type flame retardant and synergist are added, and stirred for 1 hour; the temperature is lowered to 50°C, photoinitiator is added, and stirred for 1 hour to obtain a flame retardant UV curing adhesive.

[0038] Embodiment 5:

[0039] Example 5 is different from Example 1 only in that the synergist is obtained by mixing α-zirconium phosphate and calcium metaborate in a mass ratio of 1:1, as follows: A flame retardant UV curing adhesive, comprising the following raw materials in parts by weight: 40 parts of acrylic resin, 20 parts of reactive diluent, 20 parts of polyvinyl alcohol, 10 parts of mercaptopropyl isobutyl cage silsesquioxane, 3 parts of photoinitiator, 10 parts of PN type flame retardant, 3 parts of synergist, and 0.5 parts of defoamer; The active diluent is isooctyl acrylate; the photoinitiator is 1-hydroxycyclohexyl phenyl ketone; the PN flame retardant is prepared by Preparation Example 1; the synergist is prepared by mixing α-zirconium phosphate and calcium metaborate in a mass ratio of 1:1; the defoamer is BYK-051; A method for preparing a flame retardant UV curing adhesive comprises the following steps: According to the formula, acrylic resin, active diluent and defoamer are mixed, the temperature is raised to 50°C, stirred for 1 hour, the temperature is raised to 80°C, polyvinyl alcohol, mercaptopropyl isobutyl cage silsesquioxane, PN type flame retardant and synergist are added, and stirred for 1 hour; the temperature is lowered to 50°C, photoinitiator is added, and stirred for 1 hour to obtain a flame retardant UV curing adhesive.

[0040] Embodiment 6:

[0041] Example 6 is different from Example 1 only in that the synergist is obtained by mixing organic bentonite and calcium metaborate in a mass ratio of 1:1, as follows: A flame retardant UV curing adhesive, comprising the following raw materials in parts by weight: 40 parts of acrylic resin, 20 parts of reactive diluent, 20 parts of polyvinyl alcohol, 10 parts of mercaptopropyl isobutyl cage silsesquioxane, 3 parts of photoinitiator, 10 parts of PN type flame retardant, 3 parts of synergist, and 0.5 parts of defoamer; Wherein, the active diluent is isooctyl acrylate; the photoinitiator is 1-hydroxycyclohexyl phenyl ketone; the PN flame retardant is prepared by Preparation Example 1; the synergist is prepared by mixing organic bentonite and calcium metaborate in a mass ratio of 1:1; the defoamer is BYK-051; A method for preparing a flame retardant UV curing adhesive comprises the following steps: According to the formula, acrylic resin, active diluent and defoamer are mixed, the temperature is raised to 50°C, stirred for 1 hour, the temperature is raised to 80°C, polyvinyl alcohol, mercaptopropyl isobutyl cage silsesquioxane, PN type flame retardant and synergist are added, and stirred for 1 hour; the temperature is lowered to 50°C, photoinitiator is added, and stirred for 1 hour to obtain a flame retardant UV curing adhesive.

[0042] Embodiment 7:

[0043] Example 7 is different from Example 1 only in that the synergist is obtained by mixing α-zirconium phosphate, organic bentonite and calcium metaborate in a mass ratio of 1:1:1, and is specifically as follows: A flame retardant UV curing adhesive, comprising the following raw materials in parts by weight: 40 parts of acrylic resin, 20 parts of reactive diluent, 20 parts of polyvinyl alcohol, 10 parts of mercaptopropyl isobutyl cage silsesquioxane, 3 parts of photoinitiator, 10 parts of PN type flame retardant, 3 parts of synergist, and 0.5 parts of defoamer; The active diluent is isooctyl acrylate; the photoinitiator is 1-hydroxycyclohexyl phenyl ketone; the PN flame retardant is prepared by Preparation Example 1; the synergist is prepared by mixing α-zirconium phosphate, organic bentonite and calcium metaborate in a mass ratio of 1:1:1; the defoamer is BYK-051; A method for preparing a flame retardant UV curing adhesive comprises the following steps: According to the formula, acrylic resin, active diluent and defoamer are mixed, the temperature is raised to 50°C, stirred for 1 hour, the temperature is raised to 80°C, polyvinyl alcohol, mercaptopropyl isobutyl cage silsesquioxane, PN type flame retardant and synergist are added, and stirred for 1 hour; the temperature is lowered to 50°C, photoinitiator is added, and stirred for 1 hour to obtain a flame retardant UV curing adhesive.

[0044] Embodiment 8:

[0045] Example 8 is different from Example 1 only in that the synergist is obtained by mixing α-zirconium phosphate, organic bentonite and calcium metaborate in a mass ratio of 1:5:4, specifically as follows: A flame retardant UV curing adhesive, comprising the following raw materials in parts by weight: 40 parts of acrylic resin, 20 parts of reactive diluent, 20 parts of polyvinyl alcohol, 10 parts of mercaptopropyl isobutyl cage silsesquioxane, 3 parts of photoinitiator, 10 parts of PN type flame retardant, 3 parts of synergist, and 0.5 parts of defoamer; The active diluent is isooctyl acrylate; the photoinitiator is 1-hydroxycyclohexyl phenyl ketone; the PN flame retardant is prepared by Preparation Example 1; the synergist is prepared by mixing α-zirconium phosphate, organic bentonite and calcium metaborate in a mass ratio of 1:5:4; the defoamer is BYK-051; A method for preparing a flame retardant UV curing adhesive comprises the following steps: According to the formula, acrylic resin, active diluent and defoamer are mixed, the temperature is raised to 50°C, stirred for 1 hour, the temperature is raised to 80°C, polyvinyl alcohol, mercaptopropyl isobutyl cage silsesquioxane, PN type flame retardant and synergist are added, and stirred for 1 hour; the temperature is lowered to 50°C, photoinitiator is added, and stirred for 1 hour to obtain a flame retardant UV curing adhesive.

[0046] In order to verify the performance of the flame retardant UV curing adhesives obtained in Examples 1-8 of the present invention, the present invention sets up Comparative Examples 1-4.

[0047] Comparative Example 1: Comparative Example 1 is different from Example 1 only in that the PN type flame retardant is prepared by Preparation Example 4, specifically as follows: A flame retardant UV curing adhesive, comprising the following raw materials in parts by weight: 40 parts of acrylic resin, 20 parts of reactive diluent, 20 parts of polyvinyl alcohol, 10 parts of mercaptopropyl isobutyl cage silsesquioxane, 3 parts of photoinitiator, 10 parts of PN type flame retardant, 3 parts of synergist, and 0.5 parts of defoamer; Wherein, the active diluent is isooctyl acrylate; the photoinitiator is 1-hydroxycyclohexyl phenyl ketone; the PN type flame retardant is prepared by Preparation Example 4; the synergist is organic bentonite; the defoamer is BYK-051; A method for preparing a flame retardant UV curing adhesive comprises the following steps: According to the formula, acrylic resin, active diluent and defoamer are mixed, the temperature is raised to 50°C, stirred for 1 hour, the temperature is raised to 80°C, polyvinyl alcohol, mercaptopropyl isobutyl cage silsesquioxane, PN type flame retardant and synergist are added, and stirred for 1 hour; the temperature is lowered to 50°C, photoinitiator is added, and stirred for 1 hour to obtain a flame retardant UV curing adhesive.

[0048] Comparative Example 2: Comparative Example 2 is different from Example 1 only in that the PN flame retardant (Preparation Example 1) is replaced by an equal mass of piperazine pyrophosphate, as follows: A flame retardant UV curing adhesive, comprising the following raw materials in parts by weight: 40 parts of acrylic resin, 20 parts of reactive diluent, 20 parts of polyvinyl alcohol, 10 parts of mercaptopropyl isobutyl cage silsesquioxane, 3 parts of photoinitiator, 10 parts of piperazine pyrophosphate, 3 parts of synergist, and 0.5 parts of defoamer; Among them, the active diluent is isooctyl acrylate; the photoinitiator is 1-hydroxycyclohexyl phenyl ketone; the synergist is organic bentonite; the defoamer is BYK-051; A method for preparing a flame retardant UV curing adhesive comprises the following steps: According to the formula, acrylic resin, active diluent and defoamer are mixed, the temperature is raised to 50°C, stirred for 1 hour, the temperature is raised to 80°C, polyvinyl alcohol, mercaptopropyl isobutyl cage silsesquioxane, piperazine pyrophosphate and synergist are added, and the mixture is stirred for 1 hour; the temperature is lowered to 50°C, a photoinitiator is added, and the mixture is stirred for 1 hour to obtain a flame retardant UV curing adhesive.

[0049] Comparative Example 3: Comparative Example 3 is different from Example 1 only in that the PN flame retardant is replaced by a synergist of equal mass, as follows: A flame retardant UV curing adhesive, comprising the following raw materials in parts by weight: 40 parts of acrylic resin, 20 parts of reactive diluent, 20 parts of polyvinyl alcohol, 10 parts of mercaptopropyl isobutyl cage silsesquioxane, 3 parts of photoinitiator, 13 parts of PN type flame retardant, and 0.5 parts of defoaming agent; Wherein, the active diluent is isooctyl acrylate; the photoinitiator is 1-hydroxycyclohexyl phenyl ketone; the PN type flame retardant is prepared by Preparation Example 1; the defoaming agent is BYK-051; A method for preparing a flame retardant UV curing adhesive comprises the following steps: According to the formula, acrylic resin, active diluent and defoamer are mixed, the temperature is raised to 50°C, stirred for 1 hour, the temperature is raised to 80°C, polyvinyl alcohol, mercaptopropyl isobutyl cage silsesquioxane and PN flame retardant are added, and stirred for 1 hour; the temperature is lowered to 50°C, photoinitiator is added, and stirred for 1 hour to obtain a flame retardant UV curing adhesive.

[0050] Comparative Example 4: Comparative Example 4 is different from Example 1 only in that the synergist is replaced by an equal mass of PN type flame retardant, as follows: A flame retardant UV curing adhesive, comprising the following raw materials in parts by weight: 40 parts of acrylic resin, 20 parts of reactive diluent, 20 parts of polyvinyl alcohol, 10 parts of mercaptopropyl isobutyl cage silsesquioxane, 3 parts of photoinitiator, 13 parts of synergist, and 0.5 parts of defoamer; Among them, the active diluent is isooctyl acrylate; the photoinitiator is 1-hydroxycyclohexyl phenyl ketone; the synergist is organic bentonite; the defoamer is BYK-051; A method for preparing a flame retardant UV curing adhesive comprises the following steps: According to the formula, acrylic resin, active diluent and defoamer are mixed, the temperature is raised to 50°C, stirred for 1 hour, the temperature is raised to 80°C, polyvinyl alcohol, mercaptopropyl isobutyl cage silsesquioxane and synergist are added, and stirred for 1 hour; the temperature is lowered to 50°C, a photoinitiator is added, and stirred for 1 hour to obtain a flame retardant UV curing adhesive.

[0051] Performance testing: 1. The PN flame retardant obtained in Preparation Example 1 was subjected to nuclear magnetic resonance hydrogen spectrum measurement to obtain Figure 1 The hydrogen spectrum shown was analyzed: 1H NMR (CDCl3, 500 MHz) δ 8.37 (s, 2H), 7.28 (s, 1H), 4.98-4.92 (m, 1H), 4.91 (d, J = 5.8 Hz, 0H), 4.64 (d, J = 6.2 Hz, 1H), 2.89 (dd, J = 11.0, 6.1 Hz, 1H), 2.81-2.72 (m, 1H), 2.67-2.59 (m, 3H), 2.47 (t, J = 5.7 Hz, 2H), 2.46-2.42 (m, 3H), 2.40 (s, 0H), 1.79 (p, J = 5.4 Hz, 2H), 1.65 (p, J = 5.7 Hz, 2H), 1.53 (t, J = 6.4 Hz, 2H), and the total number of hydrogen integrals is 14, and the characteristic peak of hydrogen in the [-NH-P = O] bond is found at 4.64, which can be used for the calibration of PN type flame retardant molecules, which fully illustrates that each PN type flame retardant molecule of the present invention contains three [-NH-P = O (OH) -O-] bonds. The specific chemical structure is as follows:

[0052] 2. The flame-retardant UV curing adhesive obtained in Examples 1-8 of the present invention and Comparative Examples 1-4 was coated on one side of a polypropylene film, and after being cured by irradiation with a 2000mj 365nm UV curing lamp for 20 minutes, it was rolled up to obtain a pressure-sensitive tape; the pressure-sensitive tape was subjected to a performance test, and the results are shown in Table 1: Refer to GB / T2792-2014 "Test method for peel strength of adhesive tape" to test the peel strength of pressure-sensitive tape; The flame retardant properties of pressure-sensitive adhesive tapes were determined with reference to the standard GB / T2408-2021 "Test methods for combustion performance of plastics - horizontal and vertical methods"; The oxygen index and dripping of pressure-sensitive adhesive tapes were determined with reference to standard GB / T2406.1-2008 "Determination of Combustion Behavior of Plastics by Oxygen Index Method".

[0053] Table 1:

[0054] It can be seen from the data shown in Table 1 above that the adhesives obtained in Examples 1-8 have high peel strength, a UL-94 vertical combustion test grade of V-0, an oxygen index of more than 35%, and no dripping during the combustion process, which are significantly better than Comparative Examples 1-4, fully demonstrating that the adhesives obtained in the present invention have good flame retardant effects, anti-dripping, excellent bonding properties, and have broad application prospects.

[0055] By comparing Example 1 with Comparative Examples 1 and 2, it can be seen that the PN type flame retardant of the present invention can significantly enhance the peel strength of the adhesive and effectively inhibit the combustion of the adhesive. By comparing Example 1 with Comparative Examples 3 and 4, it can be seen that the PN type flame retardant and the synergist synergize to jointly improve the flame retardant performance of the adhesive, so that its oxygen index reaches more than 35%, passes the UL-94 vertical combustion test V-0 level, and there is no dripping and no obvious smoke generation during the combustion process.

[0056] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.

Claims

1. A flame retardant UV curing adhesive, characterized in that: The invention comprises the following raw materials in parts by weight: 40-80 parts of acrylic resin, 20-50 parts of active diluent, 20-30 parts of polyvinyl alcohol, 10-20 parts of mercaptopropyl isobutyl cage-shaped silsesquioxane, 3-10 parts of photoinitiator, 10-20 parts of PN type flame retardant, 3-8 parts of synergist, and 0.5-2 parts of defoamer; The preparation method of the PN type flame retardant comprises the following steps: adding 1,4-bis(3-aminopropyl)piperazine to ethanol, mixing evenly, slowly adding an aqueous solution of phytic acid, and reacting at 60-70°C for 10-20 hours after the dropwise addition is completed within 5-10 minutes. After the reaction is completed, centrifuging, washing, drying, and purifying to obtain the PN type flame retardant.

2. The flame retardant UV curing adhesive according to claim 1, characterized in that: The mass ratio of the aqueous solution of 1,4-bis(3-aminopropyl)piperazine, ethanol and phytic acid is 6g:40-60g:13.2-22g; The content of phytic acid in the aqueous solution of phytic acid is 30-50wt%.

3. The flame retardant UV curing adhesive according to claim 1, characterized in that: The synergist is at least one of α-zirconium phosphate, organic bentonite and calcium metaborate.

4. The flame retardant UV curing adhesive according to claim 3, characterized in that: The synergist is obtained by mixing α-zirconium phosphate, organic bentonite and calcium metaborate in a mass ratio of 1:5:

4.

5. The flame retardant UV curing adhesive according to claim 1, characterized in that: The active diluent is at least one of isooctyl acrylate, dipropylene glycol diacrylate, isobornyl acrylate, tetraethylene glycol dimethacrylate, neopentyl glycol diacrylate, diethylene glycol diacrylate, glycidyl methacrylate, and dodecyl methacrylate.

6. The flame retardant UV curing adhesive according to claim 1, characterized in that: The photoinitiator is at least one of 1-hydroxycyclohexyl phenyl ketone, 2-hydroxy-2-methylphenyl acetone, (2,4,6-trimethylbenzoyl) diphenyl phosphine oxide, ethyl 2,4,6-trimethylbenzoyl phenyl phosphonate, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy) phenyl]-1-propanone and benzophenone.

7. The flame retardant UV curing adhesive according to claim 1, characterized in that: The defoaming agent is at least one of BYK-051, BYK-530, BYK-025, BYK-1723, BYK-1724, BYK-1611, and BYK-1617.

8. A method for preparing the flame retardant UV curing adhesive according to any one of claims 1 to 7, characterized in that: The following steps are involved: According to the formula, acrylic resin, active diluent and defoamer are mixed, heated to 50-70°C, stirred for 1-2 hours, heated to 80-90°C, polyvinyl alcohol, mercaptopropyl isobutyl cage silsesquioxane, PN flame retardant and synergist are added, and stirred for 1-2 hours; cooled to 50-75°C, photoinitiator is added, and stirred for 1-2 hours to obtain a flame retardant UV curing adhesive.

9. A flame retardant UV curing adhesive according to any one of claims 1 to 7 used in a pressure sensitive adhesive tape.

Citation Information

Patent Citations

  • Bio-based flame-retardant curing agent for epoxy resin as well as preparation method and application thereof

    CN108559062A

  • Halogen-free flame-retardant UV-cured acrylate pressure-sensitive adhesive and pressure-sensitive adhesive tape, and preparation method thereof

    CN110655872A

  • Environment-friendly flame-retardant low-sensitization ultraviolet curing adhesive and preparation method thereof

    CN114196369A

  • Phytic acid supramolecular flame retardant, preparation method and application

    CN114773615A

  • Flame-retardant UV curing adhesive as well as preparation method and application thereof

    CN115260948A